2011
DOI: 10.1021/ic200444e
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Thermally Induced Reorientations of Aromatic Solvate Molecules in Cu(hfac)2–Nitroxide Breathing Crystals and the Character of the Magnetic Anomaly

Abstract: A new group of "breathing" crystals has been synthesized. These are aromatic solvates of the copper(II) hexafluoroacetylacetonate complex with spin-labeled pyrazole Cu(hfac)(2)L·0.5Solv, where L is 2-(1-butyl-1H-pyrazol-4-yl)-4,4,5,5-tetramethyl-4,5-dihydro-1H-imidazole-3-oxide-1-oxyl and Solv is benzene, toluene, ethylbenzene, propylbenzene, butylbenzene, styrene, o-xylene, m-xylene, p-xylene, 1,4-bis(trifluoromethyl)benzene, 1-methyl-4-ethylbenzene, 1-methyl-4-vinylbenzene, 1,4-diethylbenzene, 1,2,3-trimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 55 publications
(131 reference statements)
0
53
0
Order By: Relevance
“…Our study of aromatic solvates showed that the magnetic characteristics of breathing crystals were sensitive not only to slight changes in the structure and composition of incorporated solvent molecules, but also to changes in their orientation relative to the paramagnetic fragments. 42 …”
Section: Relationship Between the Chemical Step And The Physical Propmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study of aromatic solvates showed that the magnetic characteristics of breathing crystals were sensitive not only to slight changes in the structure and composition of incorporated solvent molecules, but also to changes in their orientation relative to the paramagnetic fragments. 42 …”
Section: Relationship Between the Chemical Step And The Physical Propmentioning
confidence: 99%
“…This approach allowed us to summarize all data obtained for solvates with aromatic solvents (ethylbenzene, propylbenzene, butylbenzene, styrene, o-xylene, m-xylene, p-xylene, 1,4-bis(trifluoromethyl)benzene, [42]. Copyright 2011, American Chemical Society.…”
Section: Relationship Between the Thermally Induced Reorientation Of mentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Although the spin state of copper(II) cannot be changed, the total spin state of exchange-coupled copper(II)-nitroxide clusters can be changed. 8,9,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] The temperature dependence of the effective magnetic moment (μ eff (T )) strongly varies from compound to compound: abrupt or gradual transitions in one to three steps of different amplitudes may be observed. They are often called "breathing crystals" due to the large and reversible changes in unit cell volume occurring during magnetostructural transitions.…”
Section: Introductionmentioning
confidence: 99%